UPAYA PT. FREEPORT INDONESIA (PT. FI) DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI PAPUA MELALUI INSTITUT PERTAMBANGAN NEMANGKAWI (IPN) - T. Shakilla Althaf; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The issue of CSR in a foreign company has a major impact on an area where the company operates. Social investments made by the original company (FCX) through PT. FI most of provided benefits to the Indonesian government, especially in the education sector for the people of the Papua Province. The development of Nemangkawi Mining Institute (NMI) as a form of FCX CSR in Kuala Kencana, Papua, has created quality human resources, which have the potential to improve the living standards of the Human Development Index (HDI) Papuan Province. The research aims to understand how a MNC’s efforts in improving human development in Papua in the education sector through its CSR program to the Papuan people. This research was written using the theory of CSR where the foreign companies that carry out this CSR is PT. FI. This research was conducted using qualitative research methods with descriptive analysis. Data collection technique were carried out through secondary data sources and primary data sources, such as books, journals, online literature such as official reports from PT. FI and Papua Province Bappeda, newspapers and other literature sources. The results showed that NMI as a PT. FI CSR in the field of education has succeeded in creating a competent young generation of Papuans. The programs provided by PT. FI through NMI is in the form of training and education programs, providing LPMAK scholarship assistance aimed at Papuan children from NMI who have been accepted to work at PT. FI and other contracting companies. So, this CSR is also a form of effort by the Indonesian government and PT. FI in reducing the unemployment rate of the Papuan people as well as in preparation for the demographic bonus in 2030. Keywords: MNC’s, PT. Freeport Indonesia, CSR, Human Development, Papuan Young Generations